2015
DOI: 10.3928/00989134-20151015-03
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice Guideline: Depression Detection in Older Adults With Dementia

Abstract: Depression and dementia are the two most common psychiatric syndromes in the older adult population. Depression in older adults with and without dementia often goes unrecognized and untreated. The current guideline recommends a three-step procedure that can be used across health care settings to screen for the presence of depressive symptoms. Implementation of the evidence-based guideline requires administration of the Mini-Mental State Examination and either the Geriatric Depression Scale Short Form or Cornel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Social support from community service is crucial in reducing loneliness and social isolation, both closely associated with depression [36]. Community service also encompasses programs promoting physical and active lifestyles, vital for maintaining elderly physical and mental health [37]. Regular participation in these programs can enhance mood and alleviate depression symptoms [38].…”
Section: Discussionmentioning
confidence: 99%
“…Social support from community service is crucial in reducing loneliness and social isolation, both closely associated with depression [36]. Community service also encompasses programs promoting physical and active lifestyles, vital for maintaining elderly physical and mental health [37]. Regular participation in these programs can enhance mood and alleviate depression symptoms [38].…”
Section: Discussionmentioning
confidence: 99%
“…This again suggests that ingesting the capsules or participating in the study were effective for improving the depressive state of subjects. A correlation between cognitive impairment and depression has been reported, wherein it was shown that most patients with dementia also suffer from depression [18][19][20]. From the above, it could be postulated that balenine may improve the depressive state observed in many patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, apathy is a common clinical syndrome in persons with dementia; while this does not necessarily indicate depressive symptoms, it can limit engagement and complicate assessment. Similarly, symptoms of disorientation, difficulty concentrating, and memory loss are indicative of both cognitive decline and depression (American Psychiatric Association, 2013; Brown, Raue, & Halpert, 2015; Vieira, Brown, & Raue, 2014). As a result, a counselor might dismiss depressive symptoms in those with cognitive impairment as a symptom of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%